Distribution of Puerarin in Aqueous Two-Phase EOPO/K2HPO4/Water Systems - Huo, Qing; Gao, Wei (Asian Journal of Chemistry, 2012)
The partition behaviour of puerarin in ethylene oxide-propylene oxide random copolymer (EOPO)/K2HPO4/water systems was investigated. The optimum conditions were EOPO (SDP30) 28 %, K2HPO4 24 %, temperature-induced condition was 70 ºC and 0.5 h. Yield of puerarin could reach 42.26 %. Based on the modified model ln K/R2 = A* + b*(w"-w') + c*(w"- w')2, partition coefficients of puerarin in EOPO/K2HPO4 aqueous two-phase systems were correlated. It was found that the correlation of the experimental data was quite satisfactory.